(untitled) (TAJ: Journal of Teachers Association, 2023)
Background: The placenta of diabetic women has attracted much interest to the researchers from different disciplines, largely because it is thought that placental damage or dysfunction may be partially responsible for the unduly high incidence of perinatal complications in maternal diabetes. As postnatal placental examination is of immense significance to understand the fetal and perinatal conditions in antenatal and perinatal periods due to placental dysfunction or compromise resulting from diabetes in pregnancy. Objectives: The aim of this study was toinvestigate the morphological changes in placenta of pregestational and gestational diabetes mellitus. Methods: This cross-sectional comparative study was carried out in the Department of Anatomy, Rajshahi Medical College, Rajshahi in collaboration with the Department of Obstetrics & Gynae, Rajshahi Medical College Hospital and Diabetic Hospital Rajshahi, Bangladesh over a period of three years from January 2019 to December 2021. The study was conducted on 70 pregnant women, among them 35 women were diabetic and 35 women were non-diabetic. Then shape, weight, thickness and diameter of placenta were compared between diabetic and non-diabetic pregnant women. Data were analyzed by SPSS software, version 24 and p value < 0.05 was considered statistically significant for all tests. Results: The study revealed that majority of the diabetic mothers (54.3%) and non-diabetic mothers (60%) were within the age range of 20-30 years. The BMI of diabetic mothers was 27.7±1.8 kg/m2 and non-diabetic mothers was 26.7±1.7 kg/m2. The shape of the placenta was not affected by pregestational diabetes or GDM with oval-shaped placenta being predominant in either group (p = 0.478). Forty percent of the placenta from diabetic mothers were heavier (weighed > 500 gm) as compared to 5.7% of placenta from the non-diabetic pregnant women (p = 0.001). Over two-thirds (68.6%) of the placenta of the former group were larger (≥ 400 cc) as opposed to 14.3% of the non-diabetic mothers (p < 0.001). Thickness and diameter of the placenta were fairly comparable between the study groups (p = 0.445 and p = 0.164, respectively). Conclusion: The study concluded that placentas of diabetic mothers are significantly larger and heavier than those of the non-diabetic mothers. Thickness and diameter of the placenta were also greater in pregnant mothers with diabetes or GDM than those in non-diabetic mothers. TAJ 2023; 36: No-2: 129-134